EFFECTIVENESS COMPARISON OF MULCH TYPES WITH DRIP IRRIGATION AUTOMATION ON CELERY GROWTH PARAMETERS (Apium graveolens L.) - Dewi, Endang Purnama; Sumarsono, Joko; Megawati, Megawati (Universitas Muhammadiyah Mataram, 2025)
Celery is a leafy vegetable that has many benefits. Celery growth is greatly influenced by climatic factors because this plant requires a sufficiently cool temperature to grow well. Extreme temperatures that are too hot or too cold can reduce celery production. This study evaluated the significance of various types of mulch (plastic, straw, and no mulch) combined with an automatic drip irrigation system on the growth of celery plants (Apium graveolens L.). The main objective was to determine the effectiveness of the treatments and analyze their impact on soil microclimate conditions (temperature and humidity). The method used was a field experiment conducted 30 days after planting (DAP). A total of 60 plants were planted in each bed with three mulch treatments, all of which used drip irrigation. Observations were made every three days at 08.00 WITA, covering growth parameters (plant height, number of leaves, and number of branches) and soil microclimate parameters (temperature and humidity). The results showed that the type of mulch played an important role in modifying the microclimate and affecting celery growth. Although fertilization tended to increase plant height (although not statistically significant), straw mulch produced the highest results (approximately 10 cm). Meanwhile, the best vegetative growth (41 leaves and 2.87 branches) was achieved in the treatment without mulch that was fertilized. In terms of microclimate, plastic mulch recorded the highest soil temperature (28.29°C), while the highest soil moisture (23.66%) was observed in the combination of straw mulch without fertilizer. The results of the study show that the type of mulch effectively influences the microclimate conditions of the soil, which in turn supports celery growth. These results emphasize the importance of selecting the right mulch to create optimal conditions for celery cultivation with automatic drip irrigation.